2015
DOI: 10.1016/j.tcm.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Insights into cardiac conduction system formation provided by HCN4 expression

Abstract: Specialized myocytes of the cardiac conduction system (CCS) are essential to coordinate sequential contraction of cardiac atria and ventricles. Anomalies of the CCS can result in lethal cardiac arrhythmias, including sick sinus syndrome, and atrial or ventricular fibrillation. To develop future therapies and regenerative medicine aimed at cardiac arrhythmias, it is important to understand formation and function of distinct components of the CCS. Essential to this understanding is the development of CCS specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 78 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…Besides, lncRNA NONRATT027756 was predicted to trans-regulate HCN4 by means of miRNA sequestration. Hyperpolarization activated cyclic nucleotide gated potassium channel 4 (HCN4) shows slow kinetics of activation and inactivation, and is necessary in cardiac pacemaking and conduction processes (Liang et al, 2015;Verkerk and Wilders, 2015). Abnormalities of HCN4 may result in a variety of arrhythmias, such as atrial fibrillation, sick sinus syndrome (DiFrancesco, 2015;Ishikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, lncRNA NONRATT027756 was predicted to trans-regulate HCN4 by means of miRNA sequestration. Hyperpolarization activated cyclic nucleotide gated potassium channel 4 (HCN4) shows slow kinetics of activation and inactivation, and is necessary in cardiac pacemaking and conduction processes (Liang et al, 2015;Verkerk and Wilders, 2015). Abnormalities of HCN4 may result in a variety of arrhythmias, such as atrial fibrillation, sick sinus syndrome (DiFrancesco, 2015;Ishikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report the histological examination of CT in 13 patients with FDCM, identified by Monckeberg and Aschoff morphological criteria and positive immunostaining for the molecular marker HCN4. 11 The relatively high prevalence of CT inclusion in endomiocardial biopsy specimens (17% of 74 subjects with FDCM) may be due to the biventricular approach with withdrawal of 8 to 10 fragments per patient. In addition, CT was mostly found in biopsies from the LV, a common site of investigation in our laboratory for patients with cardiomyopathies 12 allowing an easier approach of the interventricular septum where CT branches are expected to be more represented in comparison with cardiac apex, as well as RV and LV free wall.…”
Section: Discussionmentioning
confidence: 99%
“…This current may contribute to the diastolic depolarization phase of SAN cell action potentials (DiFrancesco, 2006;Verkerk et al, 2009), and is carried by the hyperpolarization-activated cyclicnucleotide gated (Hcn) gene family, of which Hcn4 is the most predominant isoform found in the SAN (Marionneau et al, 2005;Moosmang et al, 2001;Stieber et al, 2003). Owing to its virtual absence in the WM and its abundance in the SAN area, Hcn4 has become a potent marker for the mature SAN, although its expression in the mouse and human embryonic hearts, and during pathophysiological conditions, is much broader (Liang et al, 2015a;Mommersteeg et al, 2007;Nattel et al, 2008;Sizarov et al, 2011). Mutations in HCN4 in humans are associated with bradycardia (den Hoed et al, 2013;Milano et al, 2014;Verkerk and Wilders, 2015).…”
Section: Introductionmentioning
confidence: 99%